Evidence for the transformation of switching hole traps into permanent bulk traps under negative-bias temperature stressing of high-k P-MOSFETs - Gao, Yuan (2013)
Under a given stress field, the recoverable component (R) for HfO2 p-MOSFET appears almost constant at lower temperatures but shows a progressive decrease at higher temperatures. Similar conclusion can also be obtained for HfSiON p-MOSFET. Evidence shows that the decrease in R is due to its transformation into a more permanent form (P). We show that those switching hole traps (SHTs) responsible for the R share the same origin as a portion of bulk traps responsible for the stress induced leakage current (SILC) and 1/f noise of the high-k gate p-MOSFET. When the density of SHTs is constant, no increase in 1/f noise and SILC, i.e. no apparent generation of bulk traps, is observed after NBTI stress. An increase in the SILC and 1/f noise, which implies the generation of bulk traps, is observed when part of these SHTs are transformed into relatively permanent bulk traps, allowing them to be sensed by the slow SILC and 1/f noise measurements.